Diversity of Edible Flora and Biotourism Potential Development of Botany Adventure in Turgo, Mount Merapi National Park Yogyakarta - Aisyah Hadi Ramadani; Muhammad Badrut Tamam; Heri Santoso; Thobib Hasan Al Yamini (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2020)
Turgo Hill is one of the areas of Mount Merapi National Park included in the Nature Tourism Zone which is intended for recreational purposes, tourist visits, and other activities. This research activity was carried out based on a case study conducted by Generasi Biologi Indonesia (Genbinesia) in the activities of Botany Adventure in Turgo Hill. This study objectives to determine the diversity of edible flora, analyze the potential of botany adventure bio tourism and plan strategies for special interest in botanical bio tourism in Turgo Hill. The research method used for the inventory of edible flora is carried out by exploring methods in 2 locations based on the elevation of 500 meters respectively. Analysis of potential bio tourism used descriptive methods through field observation, asked the questionnaires, and interviewed participants. The bio tourism strategy plan is compiled with the SWOT technique. The results of the study show that the diversity of edible flora along the tracking routes as many as 60 species. Based on the analysis of potential, Botany Adventure Biotourism activities are feasible in Bukit Turgo with a feasibility index of 92.15%. The highest potential is supported by the attractiveness of natural resources, accessibility, and the availability of clean water. SWOT search recommends strengthening and developing external factors to improve botanical special interest bio tourism activities in Bukit Turgo by providing special vehicles that mobilize participants, complementing facilities, especially souvenir kiosks, religious facilities, other tourism facilities, and promoting the promotion of activities.